Intelligence Skepticism on Performance Efficiency of Certified Public Accountants in Thailand - tatuy, chureerat; Pongpanpattana, Jeeraporn; Thitiyapramote, Natthanun (RMUTL Journal of Business Administration and Liberal Arts, 2022)
The objective of this study was to investigate intelligence skepticism on performance efficiency of auditors in Thailand. The data were collected from 313 auditors and used the questionnaires as a tool. The data were analyzed by using multiple correlation analysis and multiple regression analysis. The results showed that intelligence skepticism including reasonableness of the doubt, systematically researching knowledge and carefully evaluating the evidence has positive relationships on performance efficiency of auditors in Thailand. Therefore, the auditor should pay attention to the observations and professional suspicions that may cause the performance of the audit. To build public confidence that the audited financial statements are free from material misstatement. Moreover, the preparation of financial statements in accordance with the applicable financial reporting framework.